Analysis of factors related to compliance nurses in doing hand hygiene at Pertamina Bintang Amin Hospital Bandar Lampung - Hana Rizka Aulia; Dhiny Easter Yanti; Vera Yulyani (International Journal of Health Science and Technology, 2022)
Non-compliance by health workers, especially nurses, with the practice of hand hygiene was often associated with the incidence of nosocomial infections in hospitals. Nosocomial infection cases at Pertamina Bintang Amin Hospital, namely issues of phlebitis, were as much as 0.2%. The nurse compliance rate of 86.25% was still far from the target of achieving 100%. The purpose of this study was to determine the analysis of factors related to hand hygiene compliance at Pertamina Bintang Amin Hospital, Bandar Lampung. This study used a cross-sectional method. Respondents in this study were 113 nurses at Pertamina Bintang Amin Hospital. Univariate and bivariate data were analyzed using the chi-square test at a 95% confidence level, and multivariate data were analyzed using logistic regression. This study's results indicated no correlation between knowledge, availability of facilities, and supervision of the headroom. There was a correlation between the variables of attitude and motivation. The motivational variable was the most dominant influence on adherence (odds ratio exp (B) 3.310). It was expected that the hospital needs to give awards to nurses who carry out hand hygiene compliance properly and provide sanctions for nurses who do not comply with hand hygiene properly.